EFFECTIVENESS OF THE ANTIMICROBIAL TREATMENT OF TEXTILE MATERIALS FOR USE AT HOME AND IN PUBLIC SPACES - HOROKHOV, Ihor; KULISH, Irina; ASAULYUK, Tatyana; SARIBYEKOVA, Yulia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Purpose. The purpose of the work is to develop an antimicrobial composition and study the effectiveness of antimicrobial treatment of textile materials. Methodology. Polyhexamethylene guanidine chloride with bio-based antimicrobial preparations were used as the objects of the study as effective safe antimicrobial agents. The treatment of cotton fabric was carried out by impregnation with an aqueous solution of polymer and polyhexamethylene guanidine chloride and bio-based antimicrobial preparations in a finishing bath, followed by drying and thermal fixation. Changes in the structural parameters of the acrylic polymer and the number of crosslinks in the bulk of the polymer formation were determined from the property of crosslinked polymer systems to swell in solvents to a limited extent. Examination of the antimicrobial effect of textile materials was carried out by analyzing the diffusion of the fabric disk on agar after treatment with the antimicrobial composition and after washing. To determine the effectiveness of the antimicrobial action of bio-based preparations, one of the representatives of the wound microflora, the gram-positive bacterium Staphylococcus pyoqenes from the Ukrainian collection of microorganisms, was used as a test culture. Findings. The results of the study of textile materials after treatment with bio-based antimicrobial preparations and polyhexamethylene guanidine chloride are presented. An increase in the resistance of the antimicrobial effect to washing was achieved by introducing an acrylic polymer into the finishing composition, the structure formation of which was evaluated by the amount of the acetone-insoluble fraction of polymer films during extraction in solvents. The results of the study showed that the introduction of antimicrobial agents into the polymer composition increases the degree of crosslinking of the polymer film due to the use of polyhexamethylene guanidine chloride. The effectiveness of the antimicrobial action of bio-based preparations has been proven by the results of a study on a test culture of a gram-positive bacterium Staphylococcus pyoqenes, which is confirmed by the appearance of a zone of inhibition of the microorganism around the studied fabric sample. Studies using the settle plate method showed that all fabric samples treated with the antibacterial composition are characterized by a pronounced zone of microflora growth inhibition. Originality. It has been proven that an acrylic polymer-based finishing composition containing polyhexamethylene guanidine chloride and bio-based preparations provides an antimicrobial effect to a textile material and will improve the wash resistance of the antimicrobial effect by increasing the degree of crosslinking of the acrylic polymer. Practical value. The obtained results of the experiment are of practical importance for the development of new finishing compositions for imparting antimicrobial properties to textile materials.